The functional role of beta oscillations in Parkinson's disease. - Little, S; Brown, P (2014)
Modulations of beta oscillations (13-30 Hz) during normal motor control suggest that they may act to promote current motor set at the expense of new movements. These oscillations are greatly enhanced in Parkinson's disease (PD) and there is strong correlative evidence linking beta activity at rest and beta changes in response to treatment with bradykinesia and rigidity. Some evidence that this link may be mechanistically important or causal comes from studies in which either cortical or subcortical sites have been stimulated in the beta frequency range causing modest but significant slowing of movements. However, recent trials in which high frequency deep brain stimulation (DBS) has only been delivered during periods of elevated beta activity have demonstrated major clinical effects that even exceed those of standard continuous high frequency DBS. These studies suggest that beta activity may be both causally and quantitatively important in the motor impairment of PD, and demonstrate how improvements in the understanding of the pathophysiology of PD can lead to enhanced therapeutic interventions in this condition.